The role of microbial enzymes β-glucanase and α-amylase in optimising feed production for poultry - Zhanar Narmuratova; Raushan Blieva; Zhanara Suleimenova; Nurlan Akhmetsadykov; Gulbakhyt Zhumagalieva (Наукові горизонти)
With the increase in world population and higher consumption of poultry meat, the need for efficient feed production to ensure high quality and quantity of products is increasing. The main objective of the study was to find out the effect of microbial enzymes β-glucanase and α-amylase on optimising the performance of poultry feed. The method of analysis, one-way analysis of variance, chemical analysis and quantitative analysis were used in the study. A review of the work showed that enzyme analysis in the experimental feeds confirmed the determined concentrations of 44, 67 and 88 kN. The treatments significantly reduced body weight gain and feed conversion ratio throughout the evaluation period. The effect was particularly marked at K-110 kcal/kg and enzyme concentrations of 250, 350 and 450 mg/kg. Enzyme supplementation resulted in partial recovery of performance evident at various intervals including 10-17 days, 17-30 days, and 30-37 days. The enzyme supplemented groups showed positive results in body weight gain, especially at K-110 kcal/kg and enzyme concentrations of 250, 350 and 450 mg/kg, compared to the control group. The results emphasised not only the high precision of the study, but also the effectiveness of the enzymes in improving feed utilisation and maintaining bird performance under altered dietary conditions. The study of enzyme complex in feeds is of practical importance to the poultry industry, as it confirms the efficacy of enzyme supplementation in improving feed utilisation and maintaining bird performance under altered diets. The findings provided a basis for optimising diets using specific energy levels and enzyme concentrations, which can lead to improved body weight gain and FCR, promoting more efficient nutrient uptake and reducing productivity losses in birds